2022
DOI: 10.7324/jhsr.2022.724
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Nurses towards Standard Precautions of Infection Control in Government Hospitals of Sana'a City, Yemen

Abstract: Background: Hospital-associated infections are those infections acquired during the patient's stay in a hospital or after the patient has been discharged from the hospital. Healthcare professionals, nurses in particular, are constantly expose to these infections while carrying out their nursing activities. This study aimed to assess the level of knowledge and practice of the standard precautions of infection control among nurses in the selected government hospitals in Sana'a, Yemen. Methods: A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
2
Order By: Relevance
“…That 60.3% of the studied sample agree with [27] in India where they can identify Bio-Hazard Symbol depending on present many posters, billboards, and sometimes waste containers, which make this symbol familiar to the healthcare workers. Because of insufficient waste containers in hospitals of the present study or inconsistency with the amount of generated waste, half of studied sample 50.3% that disagree with [24] in Thailand that found 82% have good knowledge about filling of waste container to no more than 3/4 full, as well as 39.3% of our study participants conflict with [16] in Pakistan in which 88.5% of the total participant had good knowledge about the daily collection of medical waste, and about 54.4% of our studied sample knew about the transport of medical waste by wheeled trolleys which also conflict with a study in Yemen by [28] that showed 77.3% had knowledge about transportation vehicles. This difference in results may be attributed to the majority of our studied sample don't deal with the transportation of medical waste except housekeeping staff.…”
Section: Knowledge Of Mwm Among Healthcare Workerscontrasting
confidence: 89%
See 1 more Smart Citation
“…That 60.3% of the studied sample agree with [27] in India where they can identify Bio-Hazard Symbol depending on present many posters, billboards, and sometimes waste containers, which make this symbol familiar to the healthcare workers. Because of insufficient waste containers in hospitals of the present study or inconsistency with the amount of generated waste, half of studied sample 50.3% that disagree with [24] in Thailand that found 82% have good knowledge about filling of waste container to no more than 3/4 full, as well as 39.3% of our study participants conflict with [16] in Pakistan in which 88.5% of the total participant had good knowledge about the daily collection of medical waste, and about 54.4% of our studied sample knew about the transport of medical waste by wheeled trolleys which also conflict with a study in Yemen by [28] that showed 77.3% had knowledge about transportation vehicles. This difference in results may be attributed to the majority of our studied sample don't deal with the transportation of medical waste except housekeeping staff.…”
Section: Knowledge Of Mwm Among Healthcare Workerscontrasting
confidence: 89%
“…About the accidents of needle and sharps waste, the current study showed similar results with [19] in Iraq where 42.3% of studied sample protected themselves from experiencing injury by used needle or sharps during their work, but only 8.6% of them filled the accident form if the injury occur .This result may be due to the recapping needle practices by majority of studied sample make them experience the injury. In the same context, and because the importance of reporting any such injuries to the authorities and in order to provide treatment and support needed for injured healthcare workers, the present study showed 66.4% of the studied sample inform person in charge when injury by sharps waste, but this result disagree with [28] in Yemen that showed only 10.8% were reporting this injuries to supervisor perhaps due to their lack of treatments in their country. In relation to practices of our studied sample about liquid waste disposal, current study shows only 37.7% of them which is dissimilar with [24] in Thailand that shows 86.3% confirmed that they don't dispose liquid waste into the sewage system directly.…”
Section: Practices Of Mwm Among Healthcare Workerscontrasting
confidence: 86%